Analisis Teknik Vokal Onang Onang Dalam Ende Gordang Sambilan Pada Grup Kumala Huta Siantar Panyabungan Kabupaten Mandailing Natal - Umar Umar; Murniati Murniati; Sastra Sastra (Lembaga Pengembangan Kinerja Dosen, 2023)
This study examines the Onang onang Vocal Technique Analysis in Ende Gordang Sambilan in the Kumala Huta Siantar Panyabungan group, Mandailing Natal Regency. The purpose of this study was to determine the vocal techniques of onang onang by parende/group singers, using qualitative methods through a descriptive analysis approach. Using musicology theory, supported by vocal techniques in western music science. Data collection techniques through field observa-tions, interviews, and documentation. The application of vocal techniques seen from the posture in a standing position, dominant articulation using the letters A and O, breathing through chest breathing in medium and low tones and abdominal breathing at the beginning of high-pitched lyrics, onang onang intonation according to the original melody, head resonance and a distinc-tive nose, improvisation with the addition of ornaments in some of the lyrics, vibrato at the end of the lyrics, the spontaneity of the vocal lyrics in relation to the dialect of everyday language, and the miking technique by holding the mic with two hands. In terms of vocal techniques in western music, parende's vocal techniques cannot be forced. Onang onang as a traditional musical art, and has its own characteristics.